Implementation of enforcement provisions of the European Works Councils Recast Directive: are sanctions really 'effective, proportionate and dissuasive'? - Jagodziñski, Romuald (Brussels, 2014)
"The Recast of the European Works Councils (EWC) Directive of 2009 imposed for the first time on the Member States explicit requirements with regard to sanctions, stating that these must be ‘effective, proportionate and dissuasive’ (Recital 36). This policy brief shows the importance of proper implementation of sanctions for the overall efficiency and implementation of the goals of the EWC Recast Directive. It formulates some concrete policy recommendations for the Commission’s future implementation report on this Directive. "